1990
DOI: 10.1021/bi00496a011
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression, biochemical characterization and biological activities of the human MGSA/gro protein

Abstract: Melanoma growth stimulatory activity (MGSA) is a mitogenic protein secreted by Hs294T melanoma cells that corresponds to the polypeptide encoded by the human gro gene. The MGSA/gro cDNA has been expressed in mammalian cells and the secreted recombinant factor has been purified. Biochemical and biological characterization shows that the recombinant protein is identical with the natural protein and is devoid of posttranslational glycosylation, sulfation, and phosphorylation. The two C-terminal amino acids are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(13 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Purified MGSA, initially identified as a factor secreted by the human melanoma cell line Hs294T, was found to have the ability to mitogenically stimulate these same melanoma cells (8). Later, purified recombinant MGSA was found to be mitogenically active on melanoma cells in vitro (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Purified MGSA, initially identified as a factor secreted by the human melanoma cell line Hs294T, was found to have the ability to mitogenically stimulate these same melanoma cells (8). Later, purified recombinant MGSA was found to be mitogenically active on melanoma cells in vitro (4).…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells are capable of synthesizing and secreting MGSA (20). This expression is also shown to be strongly induced by factors involved in inflammation and to exhibit neutrophil chemotactic activity (4). An increase in vascularity is associated with tumor progression in melanocytic lesions from benign melanocytic nevi to MM (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shown to have higher homology to human MGSA/gro, which is a member of the chemokine family and also a neutrophil chemoattractant (Derynck et al, 1990), than to IL-8. Although several studies demonstrated that IL-8 Ribeiro et al, 1991;Rot, 1991) and CINC (Watanabe et al, 1991;Hirasawa et al, 1992) induced neutrophil infiltration in rats in vivo, there is, to our knowledge, no report comparing the neutrophil chemotactic activity of CINC and IL-8 in the same inflammatory model in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, we found a novel polypeptide neutrophil chemotactic factor, cytokine-induced neutrophil chemoattractant (CINC), 1 which is produced by the normal rat kidney epithelial cell line NRK-52E (3,4). According to its amino acid sequence, CINC appears to be a member of the human cytokine family that includes interleukin-8 (IL-8) and three closely related gro gene products, GRO␣ , GRO␤, and GRO␥ (melanoma growth-stimulating activity ␣, ␤, and ␥, respectively), all of which have chemotactic activities for human neutrophils (5)(6)(7)(8).…”
mentioning
confidence: 99%